Pengaruh Penerapan Electronic Procurement Dan Good Governance Terhadap Kinerja Pengadaan Barang/Jasa Pada Biro Pengadaan Barang Dan Jasa Sekretariat Daerah Provinsi Sumatera Utara - Rosidah Aini; Marlon Sihombing; Hatta Ridho (PERSPEKTIF, 2023)
The purpose of this study is to find out and understand how much influence the Implementation of e-Procurement has on the Performance of the Procurement of Goods and Services, know and understand how much influence Good Governance has on the Performance of the Procurement of Goods and Services and how much influence does the Implementation of e-Procurement and Good Governance together on the Performance of Procurement of Goods and Services. The method used in this study is a simple quantitative method of regression analysis to see how much influence the independent variables and dependent variables have. The population of this study were employees at the Bureau of Procurement of Goods and Services of the Regional Secretariat of North Sumatra Province with a total of 41 respondents. The sample uses total sampling, so the number of samples used is 41 respondents. Each respondent was given 35 statements. Data analysis using quantitative with a simple regression test tool. Based on the results of data processing, it shows that the implementation of e-Procurement has a positive and significant effect on good governance by 15.6%. While Good Governance has a positive and significant effect on the performance of the procurement of goods and services by 43.0%. And the implementation of e-Procurement and Good Governance together have a positive and significant effect on the performance of the procurement of goods and services by 39.7%. This shows that the implementation of e-Procurement and Good Governance is getting better, it will improve the performance of the procurement of goods and services.